Post-chemotherapy pneumonia in Chinese patients with diffuse large B-cell lymphoma: Outcomes and predictive model - Zhao, Jinrong; Zhang, Yan; Wang, Wei; Zhang, Wei; Zhou, Daobin (Frontiers in Oncology, 2022)
Pulmonary infections account for a large proportion of life-threatening adverse events that occur after chemotherapy in patients with diffuse large B-cell lymphoma (DLBCL); however, data on their influencing risk factors and the effects of infection are relatively limited. A total of 605 patients with DLBCL were newly diagnosed at our institution between March 2009 and April 2017, and 132 of these patients developed pneumonia after treatment (21.8%). There was a significant difference in overall survival (OS) between the pneumonia and non-pneumonia groups (hazard ratio 4.819, 95% confidence interval: 3.109–7.470, p < 0.0001), with 5-year OS of 41% and 82%, respectively. Pulmonary involvement, Eastern Cooperative Oncology Group score > 1, and hypoalbuminemia were identified as independent risk factors for the development of pneumonia. We constructed a prediction model based on these three factors, and the area under the curve was 0.7083, indicating good discrimination. This model may help clinicians develop individualized strategies for preventing and treating post-chemotherapy pneumonia in patients with DLBCL.